Management of Acute Traumatic Central Cord Syndrome: A Narrative Review. Issue 1 (May 2019) - Divi, Srikanth N.; Schroeder, Gregory D.; Mangan, John J.; Tadley, Madeline; Ramey, Wyatt L.; Badhiwala, Jetan H.; Fehlings, Michael G.; Oner, F. Cumhur; Kandziora, Frank; Benneker, Lorin M.; Vialle, Emiliano N.; Rajasekaran, Shanmuganathan; et al.
Study Design: Narrative review. Objectives: To provide an updated overview of the management of acute traumatic central cord syndrome (ATCCS). Methods: A comprehensive narrative review of the literature was done to identify evidence-based treatment strategies for patients diagnosed with ATCCS. Results: ATCCS is the most commonly encountered subtype of incomplete spinal cord injury and is characterized by worse sensory and motor function in the upper extremities compared with the lower extremities. It is most commonly seen in the setting of trauma such as motor vehicles or falls in elderly patients. The operative management of this injury has been historically variable as it can be seen in the setting of mechanical instability or preexisting cervical stenosis alone. While each patient should be evaluated on an individual basis, based on the current literature, the authors' preferred treatment is to perform early decompression and stabilization in patients that have any instability or significant neurologic deficit. Surgical intervention, in the appropriate patient, is associated with an earlier improvement in neurologic status, shorter hospital stay, and shorter intensive care unit stay. Conclusions: While there is limited evidence regarding management of ATCCS, in the presence of mechanical instability or ongoing cord compression, surgical management is the treatment of choice. Further research needs to be conducted regarding treatment strategies and patient outcomes.